2004
DOI: 10.1002/marc.200400062
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Changes during Thermosensitive Association of a Block Copolymer Consisting of LCST and UCST Blocks

Abstract: Summary: Thermosensitive association of a diblock copolymer consisting of poly(3‐dimethyl(methacryloyloxyethyl) ammonium propane sulfonate) (PdMMAEAPS), as an upper critical solution temperature (UCST) block, and poly(N,N‐diethylacrylamide) (PdEA), as a lower critical solution temperature (LCST) block, has been investigated by using IR spectroscopy. The ν(CO) and ν(SO) bands of the PdMMAEAPS block and the amide I band of PdEA block critically changed at the UCST and LCST, respectively, indicating that the seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
153
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(155 citation statements)
references
References 21 publications
2
153
0
Order By: Relevance
“…Furthermore, the combination of hydrophilicity and tolerance to high ionic strength makes polyzwitterions attractive candidates for hydrogels or viscosity modifiers in aqueous media under extreme conditions, such as oil field applications. Interestingly, many polyzwitterions show an upper critical solution temperature (UCST) in aqueous media [19,[42][43][44][45][46][47][48]. This has been exploited in recent years for designing stimuli-responsive polymer systems [49][50][51] from polyzwitterions, being reversibly sensitive to changes in temperature, ionic strength, specific ion pairing, and chemical reactions, or, more rarely, to changes in pH (see Section 4.2).…”
Section: Scheme1 Simplistic Model Of Polyampholytes (Left) and Polyzmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the combination of hydrophilicity and tolerance to high ionic strength makes polyzwitterions attractive candidates for hydrogels or viscosity modifiers in aqueous media under extreme conditions, such as oil field applications. Interestingly, many polyzwitterions show an upper critical solution temperature (UCST) in aqueous media [19,[42][43][44][45][46][47][48]. This has been exploited in recent years for designing stimuli-responsive polymer systems [49][50][51] from polyzwitterions, being reversibly sensitive to changes in temperature, ionic strength, specific ion pairing, and chemical reactions, or, more rarely, to changes in pH (see Section 4.2).…”
Section: Scheme1 Simplistic Model Of Polyampholytes (Left) and Polyzmentioning
confidence: 99%
“…RDRP techniques offer direct access to polymers bearing zwitterionic groups with previously unthinkable features, such as predefined molar masses and narrow molar mass distributions [163,[182][183][184][185][186][187][188][189] as well as well-defined functional end groups [61,166,182,[190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208]. Moreover, complex architectures, such as block copolymers [14,[46][47][48]166,167,169,173,187,, graft copolymers [164,213,237,[241][242][243][244]…”
Section: Synthesis By Chain Growth Polymerizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maeda et al [92] prepared a double-responsive diblock copolymer consisting of poly (38) as a USCT block and poly(N,N-diethylacrylamide) as an LCST block. By using FTIR and DSC techniques, the mechanism of micelles formation below USCT and above LCST based on selective hydration of the blocks at different temperatures was explained.…”
Section: Physically Induced Reversible Switch In Solutionsmentioning
confidence: 99%
“…Liu et al reported the preparation of thermosensitive PCL-PEG copolymer hydrogel, and investigated their physical-chemical properties and drug delivery behavior [16]. To the best of our knowledge, very few papers reported on copolymers composed of hydrophobic PCL and hydrophilic PSBMA segments [17][18][19].…”
Section: Introductionmentioning
confidence: 99%